EVALUATION OF ROUGHNESS, WETTABILITY, AND MORPHOLOGY OF AN YTTRIA-STABILIZED TETRAGONAL ZIRCONIA POLYCRYSTAL CERAMIC AFTER DIFFERENT AIRBORNE-PARTICLE ABRASION PROTOCOL - Abi-Rached, Filipe Oliveira [UNESP]; Martins, Samira Branco [UNESP]; Campos, Juliana Alvares [UNESP]; Fonseca, Renata Garcia [UNESP] (Elsevier B.V., 2014)
Statement of problem. Airborne-particle abrasion is an effective method of roughening a zirconia surface and promoting micromechanical interlocks with luting cements. However, the effect of different airborne-particle abrasion protocols on the micromechanical retention mechanism has been poorly investigated.Purpose. The purpose of the study was to evaluate the effect of airborne-particle abrasion protocols on the surface roughness, wettability, and morphology of an yttria-stabilized tetragonal zirconia polycrystal ceramic.Material and methods. A total of 140 zirconia specimens (14 x 14 x 1.4 mm) were made from Lava and divided into 7 groups. Their surfaces were treated as follows (n=20): as-sintered (control); airborne-particle abraded with 50-mu m Al2O3 particles; 120-mu m Al2O3 particles; 250-mu m Al2O3 particles; 30-mu m silica-coated Al2O3 particles (Rocatec Soft); 110-mu m silica-coated Al2O3 particles (Rocatec Plus); and 120-mu m Al2O3 particles followed by Rocatec Plus. The surface roughness (Ra) and wettability analyses were performed on the same specimens of each group. The test liquid used for the wettability analysis was the silane RelyX Ceramic Primer. Two additional specimens (6.0 x 6.0 x 1.0 mm) per group were prepared to evaluate the surface morphology with scanning electron microscopy. The roughness (Ra) data were analyzed by 1-way ANOVA and the Dunnett C test (alpha=.05), and the wettability data with 1-way ANOVA (alpha=.05). The Spearman correlation analysis was applied to test for a possible correlation between roughness and wettability.Results. The control group (0.35 mu m) exhibited the lowest mean roughness value (Ra), which was followed by Rocatec Soft (0.40 mu m), 50-mu m Al2O3 particles (0.52 mu m), Rocatec Plus (0.69 mu m), 120-mu m Al2O3 particles (0.80 mu m) / 120-mu m Al2O3 particles + Rocatec Plus (0.79 mu m), and 250-mu m Al2O3 particles (1.13 mu m). No significant difference was found among the groups concerning wettability. No correlation (r(s)=-0.09; P=.27) was found between the 2 dependent variables. The scanning electron microscopy analysis indicated that the different airborne-particle abrasion protocols produced differences in the morphologic patterns.Conclusions. Although roughness and morphology of the zirconia surface varied according to the airborne-particle abrasion protocol, no close relationship was found between them. The roughness increase seemed to have followed the size of the particles.